Study guides

☆☆

Q: What is 6x plus 3 equals 2x plus 5?

Write your answer...

Submit

Related questions

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

2x+9=6x-3 Therefore 4x=12 -->x=3

x would be -3

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

common it's very easy !!2x + 3 = 92x = 6x = 6/2x = 3

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

6x + 3 = 3(2x + 1)

2x + 4x + 3 = 6x + 3

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

9

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

3(2x - 1)(x - 2)

6x - 3y = 6 y= 2x + 5 replace 2x + 5 for y into the first equation 6x - 3y = 6 6x - 3(2x + 5) = 6 6x - 6x - 15 = 6 0 - 15 = 6 -15 = 6 False So the system has no solution.

6x with 3 over the x, because that is how many x's there are.

4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.

2x+y=3 is a line that has a -2 slope and 6x=9-3x is a vertical line. They will cross at one place. That is (1,2)

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

9

6x + 9 = -3 6x/3 + 9/3 = -3/3 2x + 3 = -1 2x + 3 - 3 = -1 - 3 2x = -4 2x/2 = -4/2 x = -2

The value of X in the equation 2x-1-6 5 plus 6x is -3.